0713 Association Between Obesity Indices And Obstructive Sleep Apnea Is Modified By Age In A Sex-specific Manner. (27th May 2020) - Liu, Y; Meng, L; Guan, J; Yi, H; Yin, S
Abstract: Introduction: The beneficial effects of weight loss on obstructive sleep apnea (OSA) are highly variable. Whether the variability is associated with the effects of age and sex remains unclear. This study examined this issue with large cross-sectional data. Methods: A total of 4600 adult males and 1156 females with suspected OSA were included in the study. Anthropometric measurements, polysomnographic variables, biochemical indicators, and medical history were collected for each subject. Multivariable linear regression with interaction terms was used to estimate the modification effect of age on the associations between OSA severity (assessed by apnea-hypopnea index, AHI) with obesity indices (body mass index, BMI; neck circumference, NC; waist circumference, WC) in a sex-specific manner, and vice versa. Results: BMI, NC, and WC were all positively correlated with AHI after adjusting for potential confounders in all populations. In males, these associations were much stronger and more significant in younger than older individuals ( P for interaction < 0.001). For example, a 10% increase in BMI was independently associated with a 31.6% increase in AHI for males < 40 years old, whereas the corresponding increases were 20.8% and 16.7% for males 40-60 and >60 years old, respectively. By contrast, no modification effect of age was observed in females ( P for interaction > 0.05). A 10% increase in BMI was associated with 25.6%, 26.8%, and 23.8% increases in AHI for females < 40, 40-60, and >60 years old, respectively. Conclusion: Age modifies the associations between obesity indices and OSA severity in a sex-specific manner, and vice versa. These findings may broaden the understanding of age- and sex-related heterogeneities in the pathogenic role of obesity in OSA, and may be beneficial for individualized risk evaluation and treatment management for patients with OSA. Support: This study was funded by Shanghai Municipal Commission of Science and Technology (grant number.18DZ2260200); the National Key R&D Program of China (grant number: 2017YFC0112500); Multi-Center Clinical Research Project from the School of Medicine, Shanghai Jiao Tong University (grant number: DLY201502); and the Shanghai Shen-Kang Hospital Management Center Project (grant number: SHDC12015101 and 16CR3103B).